2005
DOI: 10.1016/j.bbadis.2005.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative modification of rat eye lens proteins by peroxyl radicals in vitro: Protection by the chain-breaking antioxidants stobadine and Trolox

Abstract: In an attempt to model the processes of free radical-mediated cataractogenesis, we investigated the oxidative modification of rat eye lens proteins by peroxyl radicals generated by thermal decomposition of 2,2'-azobis(2-amidinopropane)hydrochloride (AAPH) under aerobic conditions. When incubated with AAPH, the soluble eye lens proteins precipitated in a time-dependent manner. The insolubilisation was accompanied by the accumulation of protein free carbonyls and the diminution of sulfhydryls, yet the processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 73 publications
1
20
0
3
Order By: Relevance
“…Trolox, in comparison with stobadine, was found to be a more potent inhibitor of 2,2'-azobis-2-amidinopropane (AAPH)-induced precipitation of the soluble eye lens proteins (Stefek et al, 2005). In contrary, production of free carbonyls due to protein oxidation was more efficiently inhibited by stobadine.…”
Section: Antioxidant Efficacies In Various Assay Systemsmentioning
confidence: 80%
“…Trolox, in comparison with stobadine, was found to be a more potent inhibitor of 2,2'-azobis-2-amidinopropane (AAPH)-induced precipitation of the soluble eye lens proteins (Stefek et al, 2005). In contrary, production of free carbonyls due to protein oxidation was more efficiently inhibited by stobadine.…”
Section: Antioxidant Efficacies In Various Assay Systemsmentioning
confidence: 80%
“…Studies by Regoli et al [38] on the capacities of antioxidants to scavenge different radicals demonstrated that mannitol had a much higher scavenging ability towards hydroxyl radicals, generated by the iron/ascorbate-driven Fenton reaction, than towards peroxyl radicals or peroxynitrite. Trolox has been reported to efficiently scavenge a wide variety of free radicals, including the hydroxyl radical and bioradical products arising from · OH radical interactions [39,40]. Similar to α-tocopherol, Trolox is primarily a chain-breaking antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether these alterations in the eEF-2 molecules could be prevented by vitamin E, we studied the effect of Trolox. The antioxidant activity of Trolox has previously been described [43,44] . The idea was also to establish the possible involvement of lipoperoxyl radicals in the mechanism of damage.…”
Section: Discussionmentioning
confidence: 99%